Numerical investigation of a multi-functional optical device based on graphene-silica metamaterial. Issue 11 (16th June 2016) - Liu, Huaiqing; Ren, Guobin; Gao, Yixiao; Zhu, Bofeng; Li, Haisu; Wu, Beilei; Jian, Shuisheng
Abstract: We propose a permittivity-tunable metamaterial channel, which is composed of alternative layers of graphene and silica. Optical waves can pass through the metamaterial channel only if its permittivity is tuned to zero. Taking advantage of the permittivity tunable property of the metamaterial, a multi-functional optical device, which can act as a wavelength demultiplexer, switch, and optical splitter without changing the geometric parameters has been proposed and numerically investigated by using the Finite Element Method. Owing to the permittivity tunable property of graphene, the working wavelength of the multi-functional device can be flexibly controlled by tuning the gate voltage applied on the metamaterial. This tunable ultracompact multi-functional optical device may find potential applications in highly integrated photonic circuits.